2022
DOI: 10.3390/toxics10120714
|View full text |Cite
|
Sign up to set email alerts
|

Critical Review of the Recent Literature on Organic Byproducts in E-Cigarette Aerosol Emissions

Abstract: We review the literature on laboratory studies quantifying the production of potentially toxic organic byproducts (carbonyls, carbon monoxide, free radicals and some nontargeted compounds) in e-cigarette (EC) aerosol emissions, focusing on the consistency between their experimental design and a realistic usage of the devices, as determined by the power ranges of an optimal regime fulfilling a thermodynamically efficient process of aerosol generation that avoids overheating and “dry puffs”. The majority of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 99 publications
0
15
0
Order By: Relevance
“…Similar topics are addressed in the second paper [ 14 ]. They review the literature on laboratory studies quantifying the production of potentially toxic organic by-products (carbonyls, carbon monoxide, and free radicals) in e-cigarette aerosol emissions, focusing on the consistency between their experimental design and a realistic usage of the devices.…”
mentioning
confidence: 85%
“…Similar topics are addressed in the second paper [ 14 ]. They review the literature on laboratory studies quantifying the production of potentially toxic organic by-products (carbonyls, carbon monoxide, and free radicals) in e-cigarette aerosol emissions, focusing on the consistency between their experimental design and a realistic usage of the devices.…”
mentioning
confidence: 85%
“…In product aerosol characterization, differences in design and engineering play an important role in the variability of total aerosol yield, the level of aerosol constituents, and nicotine dose [ 15 , 84 , 85 , 86 ]. Differences in aerosol composition may result in key differences in toxicant reduction between ENDS products as compared to CCs [ 14 , 26 , 84 ].…”
Section: A Proposed Framework: Chemical and Toxicological Evaluationmentioning
confidence: 99%
“…Hence, it is not surprising to find a wide diversity of results from EC emission studies in the literature, which points to the need to verify the compliance of laboratory studies with more stringent criteria of experimental quality, namely experimental reproducibility, testing devices in their proper operation ranges, and/or puffing parameters that are as close as possible to consumer usage. In two extensive reviews of 48 studies on EC emissions (12 focusing on metals [ 47 ], 36 on organic by-products [ 48 ]), we found that studies reporting concerning levels of toxic byproducts often failed to comply in various degrees with these quality criteria, which renders them totally or partially unreliable, while toxic byproducts remained negligible (well below their levels in tobacco smoke and toxicological markers) in all studies complying with these criteria.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The authors did not generate aerosols following a standard protocol or commercial puffing machine but used unidentified instruments designed at their site. As for the puffing regime, they followed the ISO standard for puffing volume (ISO 3308:2018) [ 48 ], with two puffs per minute and a total of fourteen puffs. As for the analytical method, it is not clear from the article what method was followed.…”
Section: Carbonyls In Emissions From Htps (Independent Studies)mentioning
confidence: 99%
See 1 more Smart Citation